Case Report: Technical description and clinical evaluation of three cases of unilateral biportal endoscopic decompression for symptomatic spinal epidural lipomatosis - Liu, Zhengqiang; Cai, Huili; Zhao, Hongwei; Tang, Lei; Jia, Siyu; Zhou, Zhenyu; Zhuo, Can; Chen, Haidan (Frontiers in Surgery, 2024)
To investigate the clinical characteristics and outcomes of three patients with symptomatic Spinal epidural lipomatosis (SEL) treated using Unilateral Biportal Endoscopic (UBE) surgery.This report retrospectively analyzed the clinical data of three patients with SEL admitted to our hospital. The analysis covers onset characteristics, clinical manifestations, and the most recent radiologic grading system of neural compression (Manjila classification). Furthermore, it details the decompression accomplished through the application of a minimally invasive UBE surgical technique, specifically targeting the removal of proliferated fat responsible for nerve and spinal cord compression.This technique was performed successfully in 3 patients with SEL. Radiating pain was reduced, and the functional disability and radiologic compression were improved in all three patients.Postoperative spinal instability and surgical complications related to the procedure were not observed.For SEL, timely diagnosis and appropriate intervention can prevent the progression of neurological disability. UBE is a minimally invasive muscle-preserving technique that achieves neural decompression directly by the removal of excessive intraspinal adipose tissue buildup.